Best Practices in Facilitating Group Work: Research Theory and Practical Examples - Kuhrasch, Cindy; Halverson, Erica; Schmidt, Lindsey (My University, 2009)
In this session, panel presenters will share best practices in facilitating group work with a combination of formal research and practical examples from our campus. The panel will be guided by research and theory on selecting the appropriate assignment, managing group formation and dynamics, facilitating group process and creating fair assessments. Participants will come away from the session with ideas and strategies that can be implemented to make group projects more productive and enjoyable.
Presentation for the Symposium for Teaching and Learning Excellence, University of Wisconsin-Madison, 26 February 2009.